Economic Effects of the Syrian War and the Spread of the Islamic State on the Levant - Ianchovichina, Elena (World Bank, Washington, DC, 2014)
This paper uses a global computable general-equilibrium framework with new detail on six Levant countries -- the Arab Republic of Egypt, Iraq, Jordan, Lebanon, the Syrian Arab Republic, and Turkey -- to quantify the direct and indirect economic effects of the Syrian war and the advance of the Islamic State on the Levant. Syria and Iraq bear the brunt of the direct economic costs, while the other Levant countries lose in per capita but not in aggregate terms. The fact that the Islamic State's spread has undermined regional trade adds to varying degrees to the direct costs in all Levant economies and in the case of Syria and Iraq doubles the welfare losses. All these countries are foregoing opportunities to expand intra-Levant trade and the associated gains in economic efficiency and diversification. The average welfare effects are not indicative of within-country incidence, which varies among workers, landowners, and capitalists.